Reversible Pore Size Control of Elastic Microporous Material by Mechanical Force. Issue 39 (28th August 2013) - Ito, Masashi; Nishihara, Hirotomo; Yamamoto, Kentaro; Itoi, Hiroyuki; Tanaka, Hideki; Maki, Akira; Miyahara, Minoru T.; Yang, Seung Jae; Park, Chong Rae; Kyotani, Takashi
Abstract Nanoporous materials, such as zeolites, activated carbons, and metal–organic frameworks (MOFs), are peculiar platforms in which a variety of guest molecules are stored, reacted, and/or separated. The size of the nanopores is essential to realize advanced functions. In this work, we demonstrate a very simple but innovative method for the control of nanopore size, that is, reversible and continuous control by mechanical force loaded to soft nanoporous materials. The elastic properties of several microporous materials, including zeolites, zeolite‐templated carbon (ZTC), activated carbon, and MOFs (e.g., ZIF‐8), are examined and it is found that ZTC is a material that is suitable for the aforementioned idea thanks to its extraordinary soft properties compared to the others. The original pore size of ZTC (1.2 nm) can be contracted to 0.85 nm by using a relatively weak loading force of 135 MPa, whereas the other microporous materials barely contracted. To demonstrate the change in the physical properties induced by such artificial deformation, in situ gas adsorption measurements were performed on ZTC with and without loading mechanical force, by using CO2, CH4, and H2, as adsorbates. Upon the contraction by loading 69 or 135 MPa, CO2 adsorption amount is increased, due to the deepening of the physisorption potential well inside the micropores, as proved by the increase of the heat of adsorption. Moreover, the adsorption amount is completely restored to the original one after releasing the mechanical force, indicating the fully reversible contraction/recovery of the ZTC framework against mechanical force. The experimental results are theoretically supported by a simulation using Grand Canonical Monte Carlo method. The similar adsorption enhancement is observed also on CH4, whereas H2 is found as an exception due to the weak interaction potential.